In vitro and in vivo anti-inflammatory activity of Phyllanthus acidus methanolic extract. (20th June 2015) - Hossen, Muhammad Jahangir; Jeon, Sung Ho; Kim, Seung Cheol; Kim, Ji Hye; Jeong, Deok; Sung, Nak Yoon; Yang, Sungjae; Baek, Kwang-Soo; Kim, Jun Ho; Yoon, Deok Hyo; Song, Won O.; Yoon, Kee Dong; et al.
Abstract: Ethnopharmacological relevance: Phyllanthus acidus (L.) Skeels (Phyllanthaceae) has traditionally been used to treat gastric trouble, rheumatism, bronchitis, asthma, respiratory disorders, and hepatitis. Despite this widespread use, the pharmacological activities of this plant and their molecular mechanisms are poorly understood. Therefore, we evaluated the immunopharmacological activities of the methanolic extract of the aerial parts of this plant (Pa-ME) and validated its pharmacological targets. Materials and methods: Lipopolysaccharide (LPS)-treated macrophages, an HCl/EtOH-induced gastritis model, and an acetic acid-injected capillary permeability mouse model were employed to evaluate the anti-inflammatory activity of Pa-ME. Potentially active anti-inflammatory components of this extract were identified by HPLC. The molecular mechanisms of the anti-inflammatory activity were studied by kinase assays, reporter gene assays, immunoprecipitation analysis, and overexpression of target enzymes. Results: Pa-ME suppressed the production of nitric oxide (NO) and prostaglandin E2 (PGE2 ) and prevented morphological changes in LPS-treated RAW264.7 cells. Moreover, both HCl/EtOH-induced gastric damage and acetic acid-triggered vascular permeability were restored by orally administered Pa-ME. Furthermore, this extract downregulated the expression of inducible NO synthase (iNOS) and cyclooxygenase (COX)-2 and reduced the nuclear levels of NF-κB. Signalling events upstream of NF-κB translocation, such as phosphorylation of Src and Syk and formation of Src/Syk signalling complexes, were also inhibited by Pa-ME. The enzymatic activities of Src and Syk were also suppressed by Pa-ME. Moreover, Src-induced and Syk-induced luciferase activity and p85/Akt phosphorylation were also inhibited by Pa-ME. Of the identified flavonoids, kaempferol and quercetin were revealed as partially active anti-inflammatory components in Pa-ME. Conclusion: Pa-ME exerts anti-inflammatory activity in vitro and in vivo by suppressing Src, Syk, and their downstream transcription factor, NF-κB. Graphical abstract: